(untitled) (Indian Journal of Animal Production and Management, 2025)
The present study was conducted to investigate the effect of supplementation of prebiotics mannan-oligosaccharide (MOS) on antioxidant and thyroid status in SVVU T17 crossbred pigs. Twenty-four SVVU T17 crossbred male grower pigs above 2 months of age were randomly divided into four groups with six piglets in each group i.e., P0, P1, P2 and P3 groups. The experiment was conducted for 45 days and at the end of experiment blood samples were collected for estimation of antioxidants and thyroid levels. There was a significant increase (P<0.05) in Catalase, SOD and GSH-Px enzymes level with raise in MOS concentration in basal diet, whereas MDA levels were significantly (P<0.05) decreased exclusively in P2 and P3. Triiodothyronine levels were not influenced by MOS inclusion in grower diets but Thyroxin hormone levels were significantly (P<0.05) decreased in all groups irrespective of MOS inclusion, whereas TSH hormone levels were raised in P3 group but P1 and P2 groups were in same range with control groups. In conclusion, MOS had a positive influence on antioxidant enzyme (Catalase, SOD and GSH-Px) levels by reducing oxidative stress (MDA levels) significantly (P<0.05), whereas a significant decrease in T4 hormone and increase in TSH levels in SVVU T17 crossbred pigs.